Analysis of 16 different matrix metalloproteinases (MMP-1 to MMP-20) in the synovial membrane: different profiles in trauma and rheumatoid arthritis. Issue 11 (1st November 1999) - Konttinen, Yrjö T; Ainola, Mia; Valleala, Heikki; Ma, Jian; Ida, Hideo; Mandelin, Jami; Kinne, Raimund W; Santavirta, Seppo; Sorsa, Timo; López-Otín, Carlos; Takagi, Michiaki
Abstract : OBJECTIVE: To define the pattern of mRNA expression of all human matrix metalloproteinases (MMPs) described to date in rheumatoid arthritis (RA) and traumatic synovial membrane, in order to differentiate between a physiological tissue remodelling pattern and that associated with inflammatory tissue destruction. METHODS: Analysis of SwissProt protein and EMBL/GenBank nucleotide sequence banks, protein sequence alignment, reverse transcriptase-polymerase chain reaction and nucleotide sequencing were used. RESULTS: MMP-2 (gelatinase A), MMP-3 (stromelysin-1), MMP-11 (stromelysin-3) and MMP-19 were constitutively expressed. MMP-1 (fibroblast type collagenase), MMP-9 (gelatinase B) and MMP-14 (MT1-MMP) were expressed in all RA, but only in 55–80% of trauma samples. MMP-13 (collagenase-3) and MMP-15 (MT2-MMP) were expressed exclusively in RA (80–90% of the samples). MMP-20 (enamelysin) was absent and MMP-8 (collagenase-2) was rarely found in RA or trauma. All other MMPs (-7, -10, -12, -16, -17) had an intermediate pattern of expression. CONCLUSIONS: Some MMPs without interstitial collagenase activity seem to have a constitutive pattern of expression and probably participate in physiological synovial tissue remodelling. Some MMPs are exclusively associated to RA synovitis, for example, MMP-13, which preferentially degrades type II collagen and aggrecan, and MMP-15, which activates proMMP-2 and proMMP-13 and is involved in tumour necrosis factor α processing. This clear cut rheumatoid/inflammatory MMP profile, more complex than has been previously appreciated, may facilitate inflammatory tissue destruction in RA.